Prosthetic hand control: A multidisciplinary review to identify strengths, shortcomings, and the future. (August 2019) - Kumar, Dinesh K.; Jelfs, Beth; Sui, Xiaohong; Arjunan, Sridhar P.
Abstract: Prosthetic hand control has fired the imagination of many researchers and thousands of papers have been published in this field, but the user acceptance has not been strong and there appears to be a significant gap between the published research and its translation. One observation of the literature is that while this requires multidisciplinary research, most articles appear to be topic focused, with lack of literature that connect across the different disciplines. This paper reports a multidisciplinary, candid review which has evaluated literature of four major associated topics: (i) User requirements, (ii) Signal recording, (iii) Signal analysis and (iv) User feedback, with the aim to identify the potential directions for research that will improve the translation of this technology. Special effort was made to collate diverse views and authors. This review has found that more research for the analysis and evaluation of the user requirements is necessary to ensure that the amputees use these devices extensively. Further research is also required into the development of both, the paradigm and the technology to give feedback to the user from the prosthetic hand device. There is also the need to improve the electrodes and recording techniques to ensure uninterrupted user-control over extended periods of time. One important outcome of this paper is that it has uncovered the differences of performance measures used by different authors because of which it is difficult to compare the results reported in their papers.